Outcomes from Penetrating Ballistic Cervical Injury. Issue 2 (1st June 2012) - Breeze, J; Masterson, L; Banfield, G
Abstract : Aims: Ballistic cervical injury has become a significant source of both morbidity and mortality for the deployed UK soldier.The aim of this paper was to document a case series of ballistic cervical wounds to describe the pattern of these injuries and relate them to outcome. Methods: The records of all UK service personnel sustaining wounds to the neck in Iraq or Afghanistan between 01 August 2004 and 01 January 2008 were analysed following identification by the Joint Theatre Trauma Registry. Blunt or thermal injuries were excluded. Results: The records of 75/76 service personnel sustaining penetrating cervical injury during this period were available for analysis. 56/75 (75%) were due to explosive fragmentation and the remainder due to gunshot wounds (GSW). 33/75 (44%) of soldiers sustained vascular injury, 32/75 (43%) injury to the spine or spinal cord, 29/75 (39%) injury to the larynx or trachea and 11/75 (15%) injury to the pharynx or oesophagus. 14/75 (19%) patients in this series underwent surgery in a hospital facility for treatment of potentially life threatening cervical injuries, with a survival rate after surgery of 12/14 (86%). The overall mortality from this series of battlefield penetrating neck injury was 63%. Conclusions: Penetrating cervical ballistic injury is a significant source of injury to deployed UK service personnel, predominantly due to neurovascular damage. Neck collars if worn would likely prevent many of the injuries in this case series but such protection is uncomfortable and may interfere with common military tasks. Newer methods of protecting the neck should be investigated that will be acceptable to the deployed UK soldier.